KARAKTERISASI TANAMAN AGLAONEMA DI DATARAN TINGGI REJANG LEBONG - Mardia Mardia Apriansi; Rini Suryani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2019)
Aglaonema in Indonesia has 30 species of diverse colors, currently Aglaonem which has color-irradiated leaves is a trend center for ornamental plant lovers. Rejang Lebong is a hilly area, has a variety of soil types, the average rainfall is 233.75 mm / month, the normal normal temperature is 17.73ºC - 30.94ºC, with physical conditions like this Rejang Lebong has various types of plants both agricultural crops, plantations, medicines, protective plants and ornamental plants. The purpose of this study was to determine the presence of germplasm, characterize and collect Aglaonema plants in the Rejang Lebong plateau. The method in this research is a survey method. Data were analyzed descriptively. The results showed that the presence of germplasm of the aglaonema plant found in the Rejang Lebong plateau, was characterized by 37 variants of the aglaonema plant in the Rejang Lebong plateau, and very minimal species of aglaonema found in the Rejang Lebong plateau posed a threat to the scarcity of Aglaonema plants, especially the type of Aglaonema species.